2020
DOI: 10.1016/j.ijhm.2019.102419
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perceived benefits and risks on current and desired levels of outsourcing: Hotel managers’ perspective

Abstract: The current paper investigates the interactions between perceived benefits and risks of outsourcing and outsourcing adoption from hoteliers' perspective. It is basically argued that, managers' perceived benefits and risks of outsourcing shape its adoption levels; both currently and in the future. Utilizing a representative sample of hotels in Egypt, the current study collected data from 123 hotels using a 32-hotel activity list. The results indicated that although managers' perceived benefits of outsourcing ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…Before analyzing the results, it should be kept in mind that outsourcing in Egypt is in its infancy, which means that hotels are now examining and testing outsourcing strategies in an attempt to maximize their profits, reduce their risks, and exchange information and experiences with these companies [115]. For this reason, the conclusions obtained are just referred to the Egyptian hotel sector as the outsourcing practice might hold other different characteristics in other tourist For hypotheses H2a and H2b about the influence of the group culture on the level of outsourcing and sustainable performance, the results show that this culture does not significantly influence the level of outsourcing (β = 0.001, p > 0.05), but it has some positive influence, with 10% significance, on sustainable performance (β = 0.135, p < 0.10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before analyzing the results, it should be kept in mind that outsourcing in Egypt is in its infancy, which means that hotels are now examining and testing outsourcing strategies in an attempt to maximize their profits, reduce their risks, and exchange information and experiences with these companies [115]. For this reason, the conclusions obtained are just referred to the Egyptian hotel sector as the outsourcing practice might hold other different characteristics in other tourist For hypotheses H2a and H2b about the influence of the group culture on the level of outsourcing and sustainable performance, the results show that this culture does not significantly influence the level of outsourcing (β = 0.001, p > 0.05), but it has some positive influence, with 10% significance, on sustainable performance (β = 0.135, p < 0.10).…”
Section: Discussionmentioning
confidence: 99%
“…Before analyzing the results, it should be kept in mind that outsourcing in Egypt is in its infancy, which means that hotels are now examining and testing outsourcing strategies in an attempt to maximize their profits, reduce their risks, and exchange information and experiences with these companies [115]. For this reason, the conclusions obtained are just referred to the Egyptian hotel sector as the outsourcing practice might hold other different characteristics in other tourist destinations.…”
Section: Discussionmentioning
confidence: 99%
“…The green initiative represents a major determinant of corporate image because it reflects the firms’ concern for the well-being of society and ethical issues, which in turn formulates a better positive image about the firm among consumers (Elhoushy et al, 2019; Ko et al, 2013; Ward & Lewandowska, 2008), and at the same time avoids the punishment for neglecting environmental protection (Porter & Vander Linde, 1995). Thus, most firms try to invest efforts in implementing various corporate social responsibility activities in order to build and improve their corporate image beyond that of their market competitors (W.…”
Section: Corporate Imagementioning
confidence: 99%
“…Based on data from the OECD database (2016), we estimated that there were approximately 130,000 employees in accommodation services and travel agencies in Egypt in 2015. Following guidance by Saunder et al (2016) and Elhoushy, Salem, and Agag (), a sample of 383 (5% error margin) was suggested for populations of this size from which we distributed 1,200 questionnaires to hotels and travel agency (600 questionnaires for hotels and the same for travel agencies). For hotel staff, 467 copies were collected of which 455 were valid and usable while the remaining 12 were not valid.…”
Section: Methodsmentioning
confidence: 99%